Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan Terhadap Nilai Perusahaan: Studi Kasus Pada Perusahaan Sub Sektor Food And Baverage Yang Tercatat Di Bursa Efek Indonesia Tahun 2019-2023 - Maharani, Anisah Putri; Murti, Galuh Tresna (eProceedings of Management, 2024)
This research aims to determine the effect of profitability, liquidity and company size on the value of research on foodand beverage sector companies listed on the Indonesia Stock Exchange. The research time period used was 5 years(2019-2023). The population used in this research was 14 companies. The sampling method used was the purposivesampling method. So 70 observations were obtained. Research data was obtained from the Indonesian Stock Exchangewebsite. The data analysis technique in this research uses descriptive statistical analysis and hypothesis testing withpanel data regression analysis. With the help of E-wies 13 software. The results of this research partially show thatprofitability as measured by Return on Assets (ROA) has no effect on company value, while liquidity measured byCurrent Ratio (CR) has a positive effect on company value and Company Size has no influence on company value. Keywords-profitability, liquidity, company value.